Selected Models of Interpretation of Volition Process and Freedom of Will in Contemporary Psychology. Fulfillment of Self-motives as a Base of Development of Volitional Dispositions. - Gasiul, Henryk (Filozofia Chrześcijańska, 2013)
It is an attempt to show how the contemporary psychology interprets the volition acts and the problem of freedom of will. The author tries to determine what conditions are necessary in order to develop the skillfulness of the will and its freedom. Some psychologists try to avoid the notion of will, some others use it together with the notion of decision and intention, subject and person. Freedom of will can increase or decrease.